2023
DOI: 10.1002/ange.202216989
|View full text |Cite
|
Sign up to set email alerts
|

Hydroxylation with Unusual Stereoinversion Catalyzed by an FeII/2‐OG Dependent Oxidase and 3,6‐Diene‐2,5‐diketopiperazine Formation in the Biosynthesis of Brevianamide K

Abstract: Natural products with the 3,6‐diene‐2,5‐diketopiperazine core are widely distributed in nature; however, the biosynthetic mechanism of 3,6‐diene‐2,5‐diketopiperazine in fungi remains to be further elucidated. Through heterologous expression and biochemical investigation of an FeII/2‐oxoglutarate‐dependent oxidase (AspE) and a heme‐dependent P450 enzyme (AspF), we report that AspE, AspF and subsequent dehydration account for the formation of the 3,6‐diene‐2,5‐diketopiperazine substructure of brevianamide K from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 57 publications
(37 reference statements)
0
4
0
Order By: Relevance
“…Several experimental findings have indicated that the carbocation intermediate proposed in the catalytic mechanism is plausible for the desaturation reactions. For instance, studies on NvfI, TqaL, AspE, KabC, PIsnB, and PvcB have reported such findings. Since the feasibility of single ET between the substrate radical and Fe III –OH [in pathway (c)] is debatable from the thermodynamic perspective, we should still be cautious regarding the detailed steps in certain cases.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…Several experimental findings have indicated that the carbocation intermediate proposed in the catalytic mechanism is plausible for the desaturation reactions. For instance, studies on NvfI, TqaL, AspE, KabC, PIsnB, and PvcB have reported such findings. Since the feasibility of single ET between the substrate radical and Fe III –OH [in pathway (c)] is debatable from the thermodynamic perspective, we should still be cautious regarding the detailed steps in certain cases.…”
Section: Discussionmentioning
confidence: 91%
“…However, recent studies have reported the occurrence of stereoconfiguration-inversed hydroxylation products in the hydroxylation reaction catalyzed by two NHFe/α-KG enzymes, TqaL and AspE. 19,68 Oxygen incorporation experiments proved that the oxygen atoms of the stereoconfiguration-inversed hydroxyl group originate from H 2 O rather than from O 2 , indicating that a carbocation intermediate is formed and attacked by H 2 O from the opposite face.…”
Section: Site-directed Mutagenesis Study Identified the Residues Invo...mentioning
confidence: 99%
See 1 more Smart Citation
“…Biochemical studies have revealed the biosynthetic pathway of brevianamide K 26 , a 3,6-diene-2,5-diketopiperazine from Aspergillus species SK-28. 24 An NRPS catalyses the formation of brevianamide K from l -tryptophan and l -proline, while two oxidative enzymes followed by dehydration are responsible for alkene formation. Gene disruption, feeding experiments and enzymes assays have allowed the elucidation of the biosynthesis of pretrichlodermamide A 27 , a fungal epidithiodiketopiperazine from Trichoderma hypoxylon .…”
mentioning
confidence: 99%